Modelling the spread of COVID-19 on Malaysian contact networks for practical reopening strategies in an institutional setting - Fatimah Abdul Razak,; Expert, Paul (Penerbit Universiti Kebangsaan Malaysia, 2021)
Reopening strategies are crucial to balance efforts of economic revitalization and bringing back a sense of normalcy while mitigating outbreaks and effectively flattening the infection curve. This paper proposes practical reopening, monitoring and testing strategies for institutions to reintroduce physical meetings based on SIR simulations run on a student friendship network collected pre-COVID-19. These serve as benchmarks to assess several testing strategies that can be applied in physical classes. Our simulations show that the best outbreak mitigation results are obtained with full knowledge of contact, but are also robust to non-compliance of students to new social interaction guidelines, simulated by partial knowledge of the interactions. These results are not only applicable to institutions but also for any organization or company wanting to navigate the COVID-19 ravaged world.